Completely biodegradable plastic film prepared from modified straw through blue light and oxygen catalytic bleaching
The straw powder is modified through the oxidative bleaching method catalyzed by blue light and oxygen, which solves the problem of degradation of the biodegradable plastic performance after the addition of straw powder, achieves an efficient and environmentally friendly bleaching effect, and reduces production costs.
Patent Information
- Application Number
- CN202411433660.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, when straw powder is added to biodegradable plastics, the tensile strength and elongation at break are significantly reduced, and traditional bleaching processes have threats to the environment and human health.
By using a synergistically catalyzed oxidative bleaching method with blue light and oxygen, the straw powder is modified to remove lignin, improve the bleaching effect, and blend the modified straw powder with biodegradable polymer to prepare a completely biodegradable plastic film.
It achieves the effect of greatly improving the elongation of break while retaining high tensile strength, while avoiding environmental pollution and health risks of traditional bleaching processes and reducing production costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of resource utilization of waste straw in agriculture, and specifically relates to a completely biodegradable plastic film prepared by bleaching and modifying straw by coordinated catalytic oxidation using blue light and oxygen. Background Art
[0002] The excessive use of non-degradable plastics has created permanent garbage that is difficult to handle, causing serious harm to the ecological environment on which we depend for survival, and also bringing a serious burden to our lives.
[0003] Fully degradable plastics are an important means to solve this problem. The typical representative of biodegradable polymers is polylactic acid, which is obtained by fermenting starch to obtain lactic acid and then undergoing polymerization. Its degradation process only produces water and carbon dioxide, and its carbon emissions are relatively low. However, its production cost is high and its price is expensive, making it difficult to be widely used.
[0004] Straw is rich in cellulose, which has the advantages of good toughness, high strength and low price. However, the lignin contained in straw makes its color darker, which affects its use. In addition, the lignin in straw has a certain influence on the stable structure of plastics. The elongation at break and tensile strength both decrease with the increase of the amount of lignin added to the composite material. The polyhydroxy polysaccharides in straw cellulose and the polymer chemical structure of fully degradable plastics are very different. Straw powder cannot be directly blended with biodegradable plastics to prepare composite materials. Therefore, it is necessary to bleach and modify the straw.
[0005] At present, hypochlorite, chlorine, hydrogen peroxide, peracetic acid, ozone and the like are mainly used as the main oxidative bleaching agents in the relevant straw powder bleaching processes. Hypochlorite or chlorine bleaching will produce a large amount of toxic and harmful substances, which poses a huge threat to human health and the environment. The hydrogen peroxide bleaching process requires a higher temperature to increase the reaction rate, which causes serious damage to the straw fiber and affects its mechanical properties. Peracetic acid has poor stability and is easy to decompose. Ozone bleaching equipment is expensive, difficult to operate, and has certain hazards to the human body. Summary of the invention
[0006] The purpose of the present invention is to provide a completely biodegradable plastic film prepared by using blue light and oxygen to catalytically bleach and modify straw. By using a catalyst and blue light irradiation to oxidatively bleach and modify straw powder, the problem of serious loss of tensile strength and elongation at break of biodegradable plastics after adding straw powder is solved.
[0007] The fully biodegradable plastic film of the invention comprises the following raw materials in parts by weight: 60-90 parts of biodegradable polymer, 10-30 parts of straw, 0.5-5 parts of surface modifier, 3-10 parts of plasticizer, 0.1-0.5 parts of oxidation catalyst, 2-10 parts of oxygen and 10-30 parts of acetonitrile.
[0008] Furthermore, the above-mentioned biodegradable polymer includes any one or more of polylactic acid, polybutylene adipate / terephthalate, polycaprolactone, ethylene-vinyl acetate copolymer, polybutylene succinate, polyhydroxyalkanoate, and polyvinyl alcohol.
[0009] Furthermore, the straw is selected from any one or more of tobacco straw, wheat straw, corn straw and rice straw.
[0010] Furthermore, the surface modifier is 3-methacryloxypropyltrimethoxysilane or 3-aminopropyltriethoxysilane.
[0011] Furthermore, the plasticizing modifier is selected from any one of glycerol, ethylene glycol, epoxy soybean oil and triethanolamine.
[0012] Furthermore, the oxidation catalyst is selected from any one or more of cupric chloride, citric acid monohydrate, ferric chloride hexahydrate, copper sulfate pentahydrate, and magnesium chloride hexahydrate.
[0013] The method for preparing the fully biodegradable plastic film of the present invention comprises the following steps:
[0014] Step 1: Dry the straw and crush it into a uniform powder of 80-120 mesh.
[0015] Step 2: Put the straw powder in step 1, the oxidation catalyst and acetonitrile in a closed environment at room temperature, slowly introduce oxygen under stirring conditions, and continue stirring for 4 to 8 hours. This process is carried out under 400 to 460 nm blue light to remove lignin in the straw powder.
[0016] Step 3: The straw powder from which lignin is removed in step 2 is subjected to solid-liquid separation by a high-speed centrifuge, and the solid is dried to obtain bleached straw powder.
[0017] Step 4: Stir and mix the bleached straw powder in step 3 with the surface modifier at room temperature to perform surface modification on the bleached straw powder.
[0018] Step 5: Mix the bleached straw powder modified in step 4 with the biodegradable polymer and the plasticizing modifier in a mixer to obtain a premix.
[0019] Step 6: Add the premix in step 5 to a twin-screw extruder for granulation and extrusion to obtain pre-granulated pellets.
[0020] Step 7: Add the pre-made pellets in step 6 into a film blowing machine to blow a film, and after cooling and shaping, a completely biodegradable plastic film is obtained.
[0021] Furthermore, in the above step 2, the acetonitrile is controlled to completely immerse the straw powder.
[0022] Furthermore, in the above step 6, the extrusion temperature of the granulator is 60-210° C., the screw speed is 110-200 r / min, and the shear rate is 1800-2100 r / min.
[0023] Furthermore, in step 7 above, the extrusion temperature of the blown film is 150-220° C., and the screw speed is 30-100 r / min.
[0024] The beneficial effects of the present invention are as follows:
[0025] 1. The present invention modifies the straw after bleaching, and the oxidation catalyst does not produce harmful substances or by-products in the catalytic reaction, thereby reducing pollution to the environment and harm to operators; and the oxidation catalyst has excellent regenerative properties, and post-processing such as recycling and activation does not produce harmful substances.
[0026] 2. The straw bleaching method adopted by the present invention efficiently converts oxygen into superoxide (O2 - ), improve the effect of oxidative bleaching; superoxide will decompose into oxygen and water after the bleaching reaction, and will not produce harmful by-products; and superoxide has strong oxidizing properties and can quickly react with lignin for oxidation; the reaction temperature can also be adjusted to control the generation rate of superoxide, so as to achieve precise control of the whiteness of the straw powder after bleaching and meet the bleaching effects of different needs.
[0027] 3. The straw bleaching method of the present invention is carried out under neutral or weakly acidic conditions, which is milder than other bleaching processes. During the bleaching process, the structure of cellulose is less damaged, and the strength of the fiber can be maintained.
[0028] 4. The fully biodegradable plastic film of the present invention is added with catalytically bleached modified straw powder, which not only solves the cost problem of the fully biodegradable plastic film, but also improves the physical properties of the fully biodegradable plastic film, greatly improving the elongation at break while retaining a relatively high tensile strength. DETAILED DESCRIPTION
[0029] In order to deepen the understanding of the present invention, the present invention will be further described in conjunction with embodiments. The embodiments are only used to illustrate the present invention and do not constitute a limitation on the protection scope of the present invention.
[0030] Comparative Example 1
[0031] The raw material composition and weight of the completely biodegradable plastic film of this comparative example are: 85 kg of polybutylene adipate / terephthalate, 10 kg of tobacco straw, 1 kg of 3-methacryloxypropyltrimethoxysilane, and 3 kg of ethylene glycol.
[0032] The preparation method of the above-mentioned fully biodegradable plastic film is as follows:
[0033] Step 1: Dry 10 kg of tobacco straw and crush it into 100 mesh uniform powder.
[0034] Step 2: The tobacco straw powder in step 1 was completely mixed with 1 kg of 3-methacryloxypropyltrimethoxysilane at room temperature and stirred for 15 minutes to perform surface modification on the tobacco straw powder.
[0035] Step 3: Mix the tobacco straw powder modified in step 2 with 85 kg of polybutylene adipate / terephthalate and 3 kg of ethylene glycol in a mixer for 15 minutes to obtain a premix.
[0036] Step 4: Add the premix in step 3 to a twin-screw extruder for granulation and extrusion. The extrusion temperature is 140° C., the screw speed is 130 r / min, and the shear rate is 1800 r / min to obtain uniform pre-granulated particles with a particle size of 3 mm.
[0037] Step 5: Add the pre-granulated pellets in step 4 into a film blowing machine to blow a film. The extrusion temperature of the blown film is 150° C. and the screw speed is 40 r / min. After cooling and shaping, a completely biodegradable plastic film is obtained with a film thickness of 0.03 mm.
[0038] Example 1
[0039] The raw material composition and weight of the fully biodegradable plastic film prepared by blue light and oxygen catalytic bleaching of modified straw in this embodiment are: 85 kg of polybutylene adipate / terephthalate, 10 kg of tobacco straw, 1 kg of 3-methacryloxypropyltrimethoxysilane, 3 kg of ethylene glycol, 0.12 kg of citric acid monohydrate, 2 L of oxygen, and 15 kg of acetonitrile.
[0040] The preparation method of the above-mentioned fully biodegradable plastic film is as follows:
[0041] Step 1: Dry 10 kg of tobacco straw and crush it into 100 mesh uniform powder.
[0042] Step 2: Place the tobacco straw powder in step 1, 0.12 kg of citric acid monohydrate and 15 kg of acetonitrile in a closed environment at room temperature, slowly introduce 2 L of oxygen at a stirring rate of 100 r / min, and continue stirring for 6 hours. This process is carried out under the illumination of a blue light to remove lignin in the tobacco straw powder.
[0043] Step 3: The tobacco straw powder from which lignin is removed in step 2 is subjected to solid-liquid separation by a high-speed centrifuge, and the solid is dried in a forced air oven at 80° C. for 2 h to obtain bleached tobacco straw powder, and the acetonitrile is recovered for secondary use.
[0044] Step 4: The bleached tobacco straw powder in step 3 was completely mixed with 1 kg of 3-methacryloxypropyltrimethoxysilane at room temperature and stirred for 15 minutes to perform surface modification on the bleached tobacco straw powder.
[0045] Step 5: The bleached tobacco straw powder modified in step 4 is mixed with 85 kg of polybutylene adipate / terephthalate and 3 kg of ethylene glycol in a mixer for 10 minutes to obtain a premix.
[0046] Step 6: Add the premix in step 5 to a twin-screw extruder for granulation and extrusion. The extrusion temperature is 140° C., the screw speed is 130 r / min, and the shear rate is 1800 r / min to obtain uniform pre-granulated particles with a particle size of 3 mm.
[0047] Step 7: Add the pre-granulated pellets in step 6 to a film blowing machine to blow a film. The extrusion temperature of the blown film is 150° C. and the screw speed is 40 r / min. After cooling and shaping, a completely biodegradable plastic film is obtained with a film thickness of 0.03 mm.
[0048] Comparative Example 2
[0049] The raw material composition and weight of the completely biodegradable plastic film of this comparative example are: 76 kg of polylactic acid, 15 kg of tobacco straw, 3 kg of 3-methacryloxypropyltrimethoxysilane, and 6 kg of glycerol.
[0050] The preparation method of the above-mentioned fully biodegradable plastic film is as follows:
[0051] Step 1: 15 kg of tobacco straw was dried and crushed into a uniform powder of 100 mesh.
[0052] Step 2: The tobacco straw powder in step 1 was completely mixed with 3 kg of 3-methacryloxypropyltrimethoxysilane at room temperature and stirred for 15 minutes to perform surface modification on the tobacco straw powder.
[0053] Step 3: Mix the tobacco straw powder modified in step 2 with 76 kg of polylactic acid and 6 kg of propylene glycol in a mixer for 15 minutes to obtain a premix.
[0054] Step 4: Add the premix in step 3 to a twin-screw extruder for granulation and extrusion. The extrusion temperature is 200° C., the screw speed is 130 r / min, and the shear rate is 1800 r / min to obtain uniform pre-granulated particles with a particle size of 4 mm.
[0055] Step 5: Add the pre-granulated pellets in step 4 into a film blowing machine to blow a film. The extrusion temperature of the blown film is 210° C. and the screw speed is 50 r / min. After cooling and shaping, a completely biodegradable plastic film is obtained with a film thickness of 0.02 mm.
[0056] Example 2
[0057] The raw material composition and weight of the fully biodegradable plastic film prepared by blue light and oxygen catalytic bleaching of modified straw in this embodiment are: 76 kg of polylactic acid, 15 kg of tobacco straw, 3 kg of 3-methacryloxypropyltrimethoxysilane, 6 kg of glycerol, 0.2 kg of citric acid monohydrate, 3 L of oxygen, and 20 kg of acetonitrile.
[0058] The preparation method of the above-mentioned fully biodegradable plastic film is as follows:
[0059] Step 1: 15 kg of tobacco straw was dried and crushed into a uniform powder of 100 mesh.
[0060] Step 2: The tobacco straw powder in step 1 is mixed with 0.2 kg of citric acid monohydrate and 20 kg of acetonitrile in a closed environment at room temperature, 3 L of oxygen is slowly introduced at a stirring rate of 100 r / min, and stirring is continued for 6 hours. This process is carried out under the illumination of a blue light to remove lignin in the tobacco straw powder.
[0061] Step 3: The tobacco straw powder from which lignin is removed in step 2 is subjected to solid-liquid separation by a high-speed centrifuge, and the solid is dried in a forced air oven at 80° C. for 2 h to obtain bleached tobacco straw powder, and the acetonitrile is recovered for secondary use.
[0062] Step 4: The bleached tobacco straw powder in step 3 was completely mixed with 3 kg of 3-methacryloxypropyltrimethoxysilane at room temperature and stirred for 15 minutes to perform surface modification on the bleached tobacco straw powder.
[0063] Step 5: The bleached tobacco straw powder modified in step 4 is mixed with 76 kg of polylactic acid and 6 kg of propylene glycol in a mixer for 10 minutes to obtain a premix.
[0064] Step 6: Add the premix in step 5 to a twin-screw extruder for granulation and extrusion. The extrusion temperature is 200° C., the screw speed is 130 r / min, and the shear rate is 1800 r / min to obtain uniform pre-granulated particles with a particle size of 4 mm.
[0065] Step 7: Add the pre-granulated pellets in step 6 into a film blowing machine to blow a film. The extrusion temperature of the blown film is 210° C. and the screw speed is 50 r / min. After cooling and shaping, a completely biodegradable plastic film is obtained with a film thickness of 0.02 mm.
[0066] Comparative Example 3
[0067] The raw material composition and weight of the completely biodegradable plastic film of this comparative example are: 42 kg of polylactic acid, 18 kg of polybutylene adipate / terephthalate, 20 kg of wheat straw, 3 kg of 3-aminopropyl triethoxysilane, and 8 kg of epoxy soybean oil.
[0068] The preparation method of the above-mentioned fully biodegradable plastic film is as follows:
[0069] Step 1: Dry 20 kg of wheat straw and crush it into 100 mesh uniform powder.
[0070] Step 2: The wheat straw powder in step 1 was completely mixed with 3 kg of 3-aminopropyltriethoxysilane at room temperature and stirred for 15 minutes to perform surface modification on the wheat straw powder.
[0071] Step 3: The modified wheat straw powder in step 2 is mixed with 42 kg of polylactic acid, 18 kg of polybutylene adipate / terephthalate, and 8 kg of epoxy soybean oil in a mixer for 15 minutes to obtain a premix.
[0072] Step 4: Add the premix in step 3 to a twin-screw extruder for granulation and extrusion. The extrusion temperature is 200° C., the screw speed is 110 r / min, and the shear rate is 2100 r / min to obtain uniform pre-granulated particles with a particle size of 3 mm.
[0073] Step 5: Add the pre-granulated pellets in step 4 into a film blowing machine to blow a film. The extrusion temperature of the blown film is 210° C. and the screw speed is 60 r / min. After cooling and shaping, a completely biodegradable plastic film is obtained with a film thickness of 0.04 mm.
[0074] Example 3
[0075] The raw material composition and weight of the fully biodegradable plastic film prepared by blue light and oxygen catalytic bleaching of modified straw in this embodiment are: 42 kg of polylactic acid, 18 kg of polybutylene adipate / terephthalate, 20 kg of wheat straw, 3 kg of 3-aminopropyltriethoxysilane, 8 kg of epoxy soybean oil, 0.05 kg of copper sulfate pentahydrate, 0.2 kg of magnesium chloride hexahydrate, 5 L of oxygen, and 30 kg of acetonitrile.
[0076] The preparation method of the above-mentioned fully biodegradable plastic film is as follows:
[0077] Step 1: Dry 20 kg of wheat straw and crush it into 100 mesh uniform powder.
[0078] Step 2: The wheat straw powder in step 1 is mixed with 0.05 kg of copper sulfate pentahydrate, 0.2 kg of magnesium chloride hexahydrate, and 30 kg of acetonitrile in a closed environment at room temperature, 5 L of oxygen is slowly introduced at a stirring rate of 100 r / min, and stirring is continued for 6 hours. This process is carried out under the illumination of a blue light to remove lignin in the wheat straw powder.
[0079] Step 3: The wheat straw powder from which lignin is removed in step 2 is subjected to solid-liquid separation by a high-speed centrifuge, and the solid is dried in a forced air oven at 80° C. for 2 h to obtain bleached wheat straw powder, and the acetonitrile is recovered for secondary use.
[0080] Step 4: The bleached wheat straw powder in step 3 was completely mixed with 3 kg of 3-aminopropyltriethoxysilane at room temperature for 15 minutes to perform surface modification on the bleached wheat straw powder.
[0081] Step 5: The bleached wheat straw powder modified in step 4 is mixed with 42 kg of polylactic acid, 18 kg of polybutylene adipate / terephthalate, and 8 kg of epoxy soybean oil in a mixer for 10 minutes to obtain a premix.
[0082] Step 6: Add the premix in step 5 to a twin-screw extruder for granulation and extrusion. The extrusion temperature is 200° C., the screw speed is 110 r / min, and the shear rate is 2100 r / min to obtain uniform pre-granulated particles with a particle size of 3 mm.
[0083] Step 7: Add the pre-granulated pellets in step 6 to a film blowing machine to blow a film. The extrusion temperature of the blown film is 210° C. and the screw speed is 60 r / min. After cooling and shaping, a completely biodegradable plastic film is obtained with a film thickness of 0.06 mm.
[0084] Comparative Example 4
[0085] The raw material composition and weight of the completely biodegradable plastic film of this comparative example are: 80 kg of polyvinyl alcohol, 20 kg of corn stalks, 3.2 kg of 3-methacryloxypropyltrimethoxysilane, and 6 kg of glycerol.
[0086] The preparation method of the above-mentioned fully biodegradable plastic film comprises the following steps:
[0087] Step 1: Dry 20 kg corn stalks and crush them into 100 mesh uniform powder.
[0088] Step 2: The corn stalk powder in step 1 was completely mixed with 3.2 kg of 3-methacryloxypropyltrimethoxysilane at room temperature and stirred for 15 minutes to perform surface modification on the corn stalk powder.
[0089] Step 3: Mix the modified corn stalk powder in step 2 with 80 kg of polyvinyl alcohol and 6 kg of propylene glycol in a mixer for 15 minutes to obtain a premix.
[0090] Step 4: Add the premix in step 3 to a twin-screw extruder for granulation and extrusion. The extrusion temperature is 80° C., the screw speed is 130 r / min, and the shear rate is 1800 r / min to obtain uniform pre-granulated particles with a particle size of 4 mm.
[0091] Step 5: Add the pre-granulated pellets in step 4 into a film blowing machine to blow a film. The extrusion temperature of the blown film is 160° C. and the screw speed is 50 r / min. After cooling and shaping, a completely biodegradable plastic film is obtained with a film thickness of 0.02 mm.
[0092] Example 4
[0093] The raw material composition and weight of the fully biodegradable plastic film prepared by blue light and oxygen catalytic bleaching of modified straw in this embodiment are: 80 kg of polyvinyl alcohol, 20 kg of corn straw, 3.2 kg of 3-methacryloxypropyltrimethoxysilane, 6 kg of glycerol, 0.24 kg of citric acid monohydrate, 4 L of oxygen, and 30 kg of acetonitrile.
[0094] The preparation method of the above-mentioned fully biodegradable plastic film is as follows:
[0095] Step 1: Dry 20 kg corn stalks and crush them into 100 mesh uniform powder.
[0096] Step 2: Place the corn straw powder in step 1 in a closed environment at room temperature, add 0.24 kg of citric acid monohydrate and 30 kg of acetonitrile, slowly introduce 4 L of oxygen at a stirring rate of 80 r / min, and continue stirring for 6 hours. This process is carried out under the illumination of a blue light to remove lignin in the wheat straw powder.
[0097] Step 3: The corn straw powder from which lignin is removed in step 2 is separated into solid and liquid by a high-speed centrifuge, and the solid is dried in a forced air oven at 80° C. for 2 h to obtain bleached corn straw powder, and the acetonitrile is recovered for secondary use.
[0098] Step 4: The bleached corn stalk powder in step 3 was completely mixed with 3.2 kg of 3-methacryloxypropyltrimethoxysilane at room temperature and stirred for 15 minutes to perform surface modification on the bleached corn stalk powder.
[0099] Step 5: Mix the modified bleached corn stover powder in step 4 with 80 kg of polyvinyl alcohol and 6 kg of propylene glycol in a mixer for 15 minutes to obtain a premix.
[0100] Step 6: Add the premix in step 5 to a twin-screw extruder for granulation and extrusion. The extrusion temperature is 80° C., the screw speed is 130 r / min, and the shear rate is 1800 r / min to obtain uniform pre-granulated particles with a particle size of 4 mm.
[0101] Step 7: Add the pre-granulated pellets in step 6 to a film blowing machine to blow a film. The extrusion temperature of the blown film is 160° C. and the screw speed is 50 r / min. After cooling and shaping, a completely biodegradable plastic film is obtained with a film thickness of 0.02 mm.
[0102] According to the national standard GB / T 23774-2009, the whiteness of the straw bleached by blue light and oxygen in the above Examples 1, 3, and 4 was tested, and the data are shown in Table 1.
[0103] Table 1
[0104]
[0105] According to the national standard GB-13022-91, the mechanical properties of the fully biodegradable plastic films prepared in the above Examples 1 to 4 and Comparative Examples 1 to 4 and the fully biodegradable plastic films prepared according to steps 3, 4, and 5 of Comparative Examples 1 to 4 without adding straw (in the table, pure PBAT is polyadipate / butylene terephthalate film, pure PLA is polylactic acid film, PLA+PBAT is polylactic acid and polyadipate / terephthalate composite film, and PVA is polyvinyl alcohol film) were tested. The performance data are shown in Table 2.
[0106] Table 2
[0107]
[0108]
[0109] Through the test of mechanical properties, it was found that the tensile strength and elongation at break of the plastic film were greatly reduced after the addition of unbleached straw powder, while the addition of bleached straw powder had almost no effect on the performance of the plastic film or slightly enhanced the performance.
[0110] Due to the chemical property that polyvinyl alcohol is easily soluble in water, it is impossible to carry out underwater degradation experiments. According to the national standard GB / T41010-2021, the degradation performance of the fully biodegradable plastic films prepared in the above Examples 1 to 3 was tested, and the performance test data under simulated groundwater and simulated seawater conditions are shown in Table 3.
[0111] Table 3
[0112]
[0113] Through the test of degradation performance, the degradation rate of the plastic film added with bleached straw powder decreased significantly within 60 days, and after extending to 120 days, the loss basically remained at 12%, indicating that it has good stability under the premise of ensuring degradation conditions.
[0114] The high prices of biodegradable materials such as polylactic acid, polyadipate / butylene terephthalate have limited their large-scale application. The present invention adds straw powder modified by blue light and oxygen catalysis to the system to replace part of the raw materials to reduce costs and facilitate the application of the final product. After adding the straw powder, it was found that when the amount of straw powder added was controlled, a product with greatly improved elongation at break could be obtained while retaining a high tensile strength.
[0115] In summary, the present invention utilizes blue light and oxygen for efficient catalysis to obtain a pollution-free, stable, low-cost bleached straw powder and performs modification. After modification, the straw powder replaces part of the biodegradable polymer to obtain a completely biodegradable plastic film with the advantages of environmental protection and low cost. The finished product still has good ductility, toughness, tensile strength, elongation at break and impact strength.
[0116] The above description is only a preferred embodiment of the present invention and does not impose any other form of limitation on the invention. Those skilled in the art can make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present invention, and such modifications or equivalent substitutions should also be regarded as within the scope of protection required by the technical solution of the present invention.
Claims
1. A completely biodegradable plastic film prepared by bleaching modified straw using blue light and oxygen catalysis, characterized in that: The invention comprises the following raw materials in parts by weight: 60 to 90 parts of biodegradable polymer, 10 to 30 parts of straw, 0.5 to 5 parts of surface modifier, 3 to 10 parts of plasticizer, 0.1 to 0.5 parts of oxidation catalyst, 2 to 10 parts of oxygen and 10 to 30 parts of acetonitrile; The method for preparing the fully biodegradable plastic film comprises the following steps: Step 1: Dry the straw and crush it into a uniform powder of 80-120 mesh; Step 2: slowly introducing oxygen into the straw powder, oxidation catalyst and acetonitrile in a closed environment at room temperature under stirring, and continuously stirring for 4 to 8 hours. This process is carried out under 400 to 460 nm blue light to remove lignin in the straw powder. Step 3: The straw powder from which lignin is removed in step 2 is subjected to solid-liquid separation by a high-speed centrifuge, and the solid is dried to obtain bleached straw powder; Step 4: stirring and mixing the bleached straw powder in step 3 with the surface modifier at room temperature to perform surface modification on the bleached straw powder; Step 5: mixing the bleached straw powder modified in step 4 with the biodegradable polymer and the plasticizing modifier in a mixer to obtain a premix; Step 6: adding the premix in step 5 to a twin-screw extruder for granulation and extrusion to obtain pre-granulated particles; Step 7: Add the pre-made pellets in step 6 into a film blowing machine to blow a film, and after cooling and shaping, a completely biodegradable plastic film is obtained.
2. The fully biodegradable plastic film prepared by using blue light and oxygen catalytic bleaching to modify straw according to claim 1, characterized in that: The biodegradable polymer includes any one or more of polylactic acid, polybutylene adipate / terephthalate, polycaprolactone, ethylene-vinyl acetate copolymer, polybutylene succinate, polyhydroxyalkanoate, and polyvinyl alcohol.
3. The fully biodegradable plastic film prepared by utilizing blue light and oxygen catalytic bleaching to modify straw according to claim 1, characterized in that: The straw is selected from any one or more of tobacco straw, wheat straw, corn straw and rice straw.
4. The biodegradable plastic film prepared by utilizing blue light and oxygen catalytic bleaching to modify straw according to claim 1, characterized in that: The surface modifier is 3-methacryloxypropyltrimethoxysilane or 3-aminopropyltriethoxysilane.
5. The fully biodegradable plastic film prepared by utilizing blue light and oxygen catalytic bleaching to modify straw according to claim 1, characterized in that: The plasticizing modifier is selected from any one of glycerol, ethylene glycol, epoxy soybean oil and triethanolamine.
6. The fully biodegradable plastic film prepared by utilizing blue light and oxygen catalytic bleaching to modify straw according to claim 1, characterized in that: The oxidation catalyst is selected from any one or more of cupric chloride, citric acid monohydrate, ferric chloride hexahydrate, copper sulfate pentahydrate, and magnesium chloride hexahydrate.
7. The fully biodegradable plastic film prepared by utilizing blue light and oxygen catalytic bleaching to modify straw according to claim 1, characterized in that: In step 2, the acetonitrile is controlled to completely immerse the straw powder.
8. The fully biodegradable plastic film prepared by utilizing blue light and oxygen catalytic bleaching to modify straw according to claim 1, characterized in that: In step 6, the extrusion temperature of the granulator is 60-210° C., the screw speed is 110-200 r / min, and the shear rate is 1800-2100 r / min.
9. The fully biodegradable plastic film prepared by utilizing blue light and oxygen catalytic bleaching to modify straw according to claim 1, characterized in that: In step 7, the extrusion temperature of the blown film is 150-220° C., and the screw speed is 30-100 r / min.
Citation Information
Patent Citations
Method for preparing cellulose by using straws
CN102535224A
Method for improving anaerobic straw digestion gas production performance through photocatalytic pretreatment
CN109082446A
Completely biodegradable plastic film prepared from straws and preparation method thereof
CN112175330A
Ultrafine straw / calcium carbonate powder-based method for preparing mulch film and product prepared therefrom
WO2024103692A1